Polyester master batch suitable for low-roughness PET optical film as well as preparation method and application of polyester master batch
By adopting homogenization and centrifugal dispersion processes in the preparation of PET optical films, the problem of uneven dispersion of silica particles is solved, nano-level dispersion and optical performance improvement are achieved, and the demand for low-roughness PET optical films is met. .
Patent Information
- Application Number
- CN202411442292.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-14
AI Technical Summary
In the prior art, when preparing PET optical films, it is difficult for silica particles to reach nano-level dispersion, resulting in the inability to reach a higher level of optical performance, and the mass production of polyester masterbatches is difficult, resulting in the need to import a large number of PET optical films in China.
Using a homogenization and centrifugal dispersion process, the nano-level is achieved by adding stabilizer, catalyst and silica dispersion liquid in the pre-polycondensation stage and maintaining circulation in the esterified liquid. silica dispersion.
The dispersion effect of silica in the polyester masterbatch is improved, the optical performance of the optical film is improved, and after the film surface is formed by bidirectional stretching, the particles on the film surface are evenly distributed, and the surface roughness reaches Ra<12nm and Rz<150nm. A low roughness PET optical film is achieved.
Smart Images

Figure CN119306929A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of PET optical film materials, and in particular relates to a polyester masterbatch suitable for a low-roughness PET optical film, a preparation method and an application thereof. Background Art
[0002] New flat panel display technologies have spawned new application scenarios, such as OLED, Mini LED, Micro LED, etc. The gradual improvement of new display technologies has led to an increase in demand for optical films. China is becoming the world's largest processing and manufacturing base for the new display industry. However, China currently needs to import more than 300,000 tons of polyester film annually, a large part of which is optical film for the display field. It is urgent to develop optical films for the display field and realize industrialization.
[0003] Optical film is composed of three thin layers of medium, A, B, and C, in which polyester masterbatch is added to the A and C layers to have opening and optical properties. Optical film has been widely used in the field of optics and optoelectronics technology to manufacture various optical instruments. The main optical thin film devices include reflective film, anti-reflective film, polarizing film, interference filter, spectroscope compensation film, phase matching film, diffusion film, window film, brightness enhancement film, MLCC release film, OCA release film, etc. Among them, reflective film, window film, MLCC release film and OCA release film mostly use PET optical film. In the field of domestic PET optical film, in addition to the need for breakthroughs in the production process, the inability to mass produce polyester masterbatch is also a key factor. It is urgent to solve the dispersion technology of small-particle silica in polyester masterbatch, realize the mass production of polyester masterbatch for PET optical film, and solve the "bottleneck" problem of PET optical film.
[0004] At present, the optical film polyester masterbatch is mostly prepared by blending / copolymerization process, with silicon dioxide as the dispersion medium. For example, patent CN116021857A provides a high-definition optical polyester film and its blending preparation method, which has the characteristics of clear film surface, clear film body, low haze, good mechanical properties, thermal properties, flatness, and good surface quality. It is widely used in high-end protection / release, window film, car cover film and other fields, including the following steps: (1) pre-mixing the polyester masterbatch, modified polyester and polyethylene terephthalate slices in proportion, feeding them into the corresponding melt extrusion system, extruding at a temperature of 260℃~275℃, and entering the die for co-extrusion; (2) preparing the high-definition optical polyester film by casting, longitudinal drawing, transverse drawing, shaping, cooling, pulling and winding, wherein the polyester masterbatch contains 0.3~10 parts by weight of silicon dioxide particles and modified polyester prepared from 1,3-cyclohexanedicarboxylic acid, isophthalic acid and terephthalic acid. However, the blending process uses a screw extruder to disperse the silica particles in the molten state of polyester. It is difficult to achieve nano-level dispersion of silica particles in the prepared high-definition optical polyester, and the optical performance of the high-definition optical polyester film cannot reach a high level. Patent CN115322533A provides an MLCC release film transfer polyester masterbatch and a preparation method thereof, which adopts an intermittent process of esterification, pre-polycondensation and final polycondensation to prepare the polyester masterbatch, and adds a silica dispersion prepared by ball milling during the pre-polycondensation reaction, including the following steps: (1) terephthalic acid, ethylene glycol and a catalyst are mixed and dispersed to form a slurry; (2) the slurry is subjected to an esterification reaction to generate an esterified liquid; (3) the esterified liquid is added with a silica dispersion prepared by ball milling and a stabilizer for a pre-polycondensation reaction to generate an intermediate; (4) the intermediate is subjected to a polycondensation reaction to generate a melt; (5) the melt is sliced and packaged. In the copolymerization process, silica dispersion is added in the pre-condensation stage, and the silica is fully mixed and evenly distributed. After the MLCC release film is transferred to the polyester masterbatch and biaxially stretched into a film, the surface roughness of the film is Ra <15nm, Ra <200nm.
[0005] Although the polyester masterbatch prepared by the copolymerization process can achieve the low roughness requirement of the film after double drawing, the self-aggregation of silica in the esterification liquid in the pre-condensation stage will reduce the dispersion uniformity of the particles. Therefore, the inventors provide a polyester masterbatch and preparation process suitable for low-roughness PET optical film. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing a polyester masterbatch suitable for a low-roughness PET optical film, the preparation method comprising the following steps:
[0008] S1. Prepare stabilizer dispersion, catalyst dispersion and silicon dioxide dispersion respectively for standby use;
[0009] S2, terephthalic acid and ethylene glycol are uniformly mixed and subjected to esterification reaction at 240-255° C. and 0.3 MPa to obtain esterified liquid; when the amount of esterified water collected reaches 90%, the esterified liquid is transferred to a pre-condensation reactor;
[0010] S3, in the pre-polycondensation reactor, adding the stabilizer dispersion, the catalyst dispersion and the silica dispersion to the esterification liquid in sequence, and performing a pre-polycondensation reaction at 255-275° C. and 10-100 kPa to obtain an intermediate, and the reaction time is 30-45 min; the esterification liquid is always circulated during the pre-polycondensation reaction;
[0011] S4. The intermediate prepared by the pre-polycondensation reaction is subjected to a final polycondensation reaction at 275-285° C. and 30-50 PaA to obtain a melt, and the melt is pelletized and packaged to obtain a polyester masterbatch.
[0012] Furthermore, the mass ratio of the terephthalic acid, ethylene glycol, stabilizer dispersion, catalyst dispersion and silica dispersion is (50-70):(20-30):(1-5):(0.1-1):(0.5-25).
[0013] Furthermore, the configuration of the catalyst dispersion is specifically as follows: ethylene glycol is added to a preparation tank with an agitator, and then the catalyst is added to the ethylene glycol, heated to 130-170°C, and stirred at a speed of 250-1000m / min for 0.5-1.5h; after the stirring is completed, the material is transferred to the intermediate tank through a homogenizing and dispersing device, and after all the materials are transferred to the intermediate tank, all the materials are transferred to the preparation tank, and the materials are transferred to the intermediate tank again through the homogenizing and dispersing device, and this process is repeated 2-5 times to prepare the catalyst dispersion.
[0014] Furthermore, the mass proportion of the catalyst in the catalyst dispersion is 1-5%; the catalyst is one of antimony-based, titanium-based, germanium-based or composite catalysts.
[0015] Furthermore, the configuration of the stabilizer dispersion is specifically as follows: ethylene glycol is added into a preparation tank with a stirrer, and then the stabilizer is added into the ethylene glycol, and stirred at a speed of 250 to 1000 m / min for 0.5 to 1.5 h to prepare the stabilizer dispersion.
[0016] Furthermore, the mass proportion of the stabilizer in the stabilizer dispersion is 1-10%; the stabilizer is one of phosphoric acid, trimethyl phosphate, triethyl phosphate, and triphenyl phosphate.
[0017] Furthermore, the configuration of the silica dispersion is specifically as follows: ethylene glycol is added to a preparation tank with an agitator, and then silica is added to the ethylene glycol, and stirred at a speed of 500 to 1500 m / min for 0.5 to 2.5 hours; after the stirring is completed, the material is transferred to the intermediate tank after homogenization and dispersion, and after all the materials are transferred to the intermediate tank, all the materials are transferred to the preparation tank, and the materials are transferred to the intermediate tank again through the homogenization and dispersion equipment. This process is repeated 2 to 5 times to prepare a silica pre-dispersion liquid, and the silica pre-dispersion liquid is transferred to the finished product tank after centrifugation in a centrifuge to prepare a silica dispersion liquid; the centrifuge drum speed is 1500 to 3000 r / min, and the centrifugal force is 2000 to 3500 xg.
[0018] Furthermore, the mass proportion of silicon dioxide in the silicon dioxide dispersion is 7-15%.
[0019] A polyester masterbatch suitable for a low-roughness PET optical film is prepared by the above-mentioned method for preparing a polyester masterbatch suitable for a low-roughness PET optical film.
[0020] The polyester masterbatch suitable for low-roughness PET optical film described above is used as a raw material in the preparation of optical film materials.
[0021] Beneficial effects of the present invention:
[0022] 1. The polyester masterbatch and preparation process suitable for low-roughness PET optical film provided by the present invention adopts a homogenization and centrifugal dispersion process to improve the uniformity of the dispersion of silicon dioxide dispersion particles and enhance the concentration of particle size distribution.
[0023] 2. The polyester masterbatch and preparation process suitable for low-roughness PET optical film provided by the present invention add stabilizer dispersion, catalyst dispersion and silica dispersion in the pre-polycondensation stage to improve the mixing efficiency of the stabilizer, catalyst and silica in the pre-polycondensation stage.
[0024] 3. The polyester masterbatch and preparation process for low-roughness PET optical film provided by the present invention add an external pipeline in the pre-polycondensation stage, and the esterification liquid is always kept circulating during the pre-polycondensation reaction process. The silicon dioxide in the esterification liquid is dispersed at the nanometer level, thereby improving the dispersion effect of silicon dioxide in the polyester masterbatch;
[0025] 4. The polyester masterbatch and preparation process suitable for low-roughness PET optical film provided by the present invention has uniform particle distribution and concentrated particle size distribution on the film surface after biaxial stretching to form a film, and its surface roughness Ra is less than 12nm and Rz is less than 150nm. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0027] Figure 1 It is a schematic diagram of the polyester masterbatch suitable for low-roughness PET optical film and its preparation process flow according to the present invention;
[0028] Figure 2 This is a test chart of the silica particle size distribution of the silica dispersion prepared in the embodiment of the present invention;
[0029] Figure 3 This is a test chart of the silicon dioxide particle size distribution of the esterification liquid prepared in the embodiment of the present invention;
[0030] Figure 4 Schematic diagram of the self-circulation of the pre-polycondensation reaction esterification liquid used in the embodiment of the present invention;
[0031] Figure 5 This is a measurement diagram of the surface roughness of the PET optical film obtained in Example 1 of the present invention;
[0032] Figure 6 This is a measurement diagram of the surface roughness of the PET optical film prepared in Comparative Example 1 of the present invention;
[0033] Figure 7 This is a measurement diagram of the surface roughness of the PET optical film prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Preparation of catalyst dispersion
[0036] Add ethylene glycol to a preparation tank with an agitator, then add the catalyst to the ethylene glycol, heat to 130-170°C, and stir at a speed of 250-1000m / min for 0.5-1.5h; after the stirring is completed, the material is transferred to the intermediate tank through a homogenizing and dispersing device, and after all the materials are transferred to the intermediate tank, all the materials are transferred to the preparation tank, and the materials are transferred to the intermediate tank again through the homogenizing and dispersing device. This process is repeated 2-5 times to prepare a catalyst dispersion; the mass proportion of the catalyst in the catalyst dispersion is 1-5%.
[0037] The catalyst is one of antimony-based, titanium-based, germanium-based or composite catalysts.
[0038] Specifically, antimony catalysts include antimony trioxide, antimony acetate, and antimony glycol. In the presence of oxygen, trivalent antimony is easily reduced to antimony element, causing the polyester to turn gray. However, antimony catalysts are relatively economical, with antimony trioxide being the most economical; titanium catalysts include titanates represented by n-butyl titanate, which have good environmental friendliness and catalytic activity, but the selectivity for polycondensation and degradation reactions is not high, resulting in more polyester by-products, yellowing of polyester, and high terminal carboxyl value; germanium catalysts are rare metals, expensive but with excellent catalytic performance; composite catalysts, such as aluminum and magnesium composites, antimony and aluminum composites, etc., can actively adjust the catalyst function, increase the reaction rate while retaining high-efficiency catalysis and excellent selectivity, and reduce the generation of side reactions.
[0039] Preparation of stabilizer dispersion
[0040] Ethylene glycol is added into a preparation tank with a stirrer, and then a stabilizer is added into the ethylene glycol, and stirred at a speed of 250 to 1000 m / min for 0.5 to 1.5 hours to prepare a stabilizer dispersion; the mass proportion of the stabilizer in the stabilizer dispersion is 1 to 10%.
[0041] Specifically, the stabilizer uses a phosphorus stabilizer, specifically one of phosphoric acid, trimethyl phosphate, triethyl phosphate, and triphenyl phosphate; the phosphorus stabilizer can react with water molecules in the system, thereby reducing the degradation reaction caused by hydrolysis; the phosphorus stabilizer can react with the active substances in the polyester to close the end groups, forming a stable phosphate compound, thereby inhibiting the decomposition reaction of the polyester and extending the service life of the polyester; the phosphorus catalyst can react with the oxygen in the polyester to form a phosphorus oxygen compound, thereby inhibiting the degradation reaction of the polyester and improving the stability and durability of the polyester. However, the amount of phosphorus added should not be too high, as the reaction of excessive phosphorus with the metal of the catalyst will cause the catalyst to deactivate.
[0042] Preparation of silica dispersion
[0043] Ethylene glycol is added to a preparation tank with an agitator, and then silicon dioxide is added to the ethylene glycol, and stirred at a speed of 500-1500 m / min for 0.5-2.5 hours; after the stirring is completed, the material is transferred to an intermediate tank through homogenization and dispersion, and after all the materials are transferred to the intermediate tank, all the materials are transferred to the preparation tank, and the materials are transferred to the intermediate tank through the homogenization and dispersion equipment again. This process is repeated 2-5 times to prepare a silicon dioxide pre-dispersion liquid, and the silicon dioxide pre-dispersion liquid is transferred to a finished product tank after centrifugation in a centrifuge to prepare a silicon dioxide dispersion liquid; the centrifuge drum speed is 1500-3000 r / min, and the centrifugal force is 2000-3500 xg; the mass proportion of silicon dioxide in the silicon dioxide dispersion liquid is 7-15%.
[0044] The silica dispersion after stirring needs to be homogenized and dispersed. The homogenized and dispersed equipment is one of a homogenizing pump, a pipeline mixer, a colloid mill and a ball mill. After the materials in the configuration tank are homogenized and transferred to the intermediate tank, all the materials are transferred to the preparation tank for homogenization again to avoid the problem of uneven material processing. Repeat homogenization 2 to 5 times to prepare the silica pre-dispersion. The homogenization intensity and homogenization time directly affect the dispersion effect of silica. If the homogenization intensity is low and the homogenization time is short, the dispersion effect is poor and the homogenization efficiency is low; if the homogenization intensity is high and the homogenization time is long, the silica particles are easily broken, and the pre-dispersion is more unstable, and the particles are more likely to agglomerate, resulting in the roughness of the film surface will also increase and the optical performance will be reduced, so it is necessary to select a suitable homogenization intensity and homogenization time; the pre-dispersion after homogenization dispersion needs to be centrifuged, and the centrifuge drum speed is 1500-3000r / min and the centrifugal force is 2000-3500xg. If the centrifuge drum speed and centrifugal force are too low, larger silica particles cannot be effectively removed; if the centrifuge drum speed and centrifugal force are too high, larger silica particles with appropriate particle size will be removed from the soy milk. Therefore, it is necessary to choose the appropriate centrifuge drum speed and centrifugal force.
[0045] As an optional implementation, a dispersant may be added during the silicon dioxide dispersion treatment. The dispersant is one or more of a silane coupling agent, polyethylene wax, polyethylene glycol 200 or polyethylene glycol 400, and the mass proportion of the dispersant is 1-5%. The silicon dioxide powder has a small particle size and is easy to agglomerate, which will lead to low stability of the dispersion. A certain amount of dispersant needs to be added. The amount of dispersant should not be too much, which will not only increase the cost, but also reduce the cleanliness of the polyester.
[0046] A method for preparing a polyester masterbatch suitable for a low-roughness PET optical film, the preparation method comprising the following steps:
[0047] S1. Prepare stabilizer dispersion, catalyst dispersion and silicon dioxide dispersion respectively for standby use;
[0048] S2. Evenly mix terephthalic acid and ethylene glycol and carry out esterification reaction at 240-255° C. and 0.3 MPa to obtain esterified liquid; when the amount of esterified water collected reaches 90%, the esterified liquid is transferred to a pre-condensation reactor.
[0049] S3, in the pre-polycondensation reactor, adding the stabilizer dispersion, the catalyst dispersion and the silica dispersion to the esterification liquid in sequence, and performing a pre-polycondensation reaction at 255-275° C. and 10-100 kPa to obtain an intermediate, and the reaction time is 30-45 min; the esterification liquid is always circulated during the pre-polycondensation reaction;
[0050] S4. The intermediate prepared by the pre-polycondensation reaction is subjected to a final polycondensation reaction at 275-285° C. and 30-50 PaA to obtain a melt, and the melt is pelletized and packaged to obtain a polyester masterbatch.
[0051] The mass ratio of the terephthalic acid, ethylene glycol, stabilizer dispersion, catalyst dispersion and silicon dioxide dispersion is (50-70):(20-30):(1-5):(0.1-1):(0.5-25).
[0052] Example 1
[0053] A method for preparing a polyester masterbatch suitable for a low-roughness PET optical film, the preparation method comprising the following steps:
[0054] S1. Prepare stabilizer dispersion, catalyst dispersion and silicon dioxide dispersion respectively for standby use;
[0055] S2. Evenly mix terephthalic acid and ethylene glycol and carry out esterification reaction at 255° C. and 0.3 MPa to obtain esterified liquid; when the amount of esterified water collected reaches 90%, the esterified liquid is transferred to a pre-condensation reactor.
[0056] S3, adding stabilizer dispersion, catalyst dispersion and silica dispersion to the esterification liquid in a pre-polycondensation reactor, and performing a pre-polycondensation reaction at 275° C. and 100 kPa to obtain an intermediate, and the reaction time is 30 min; the esterification liquid is always circulated during the pre-polycondensation reaction;
[0057] S4. The intermediate prepared by the pre-polycondensation reaction is subjected to a final polycondensation reaction at 285° C. and 50 PaA to obtain a melt, and the melt is pelletized and packaged to obtain a polyester masterbatch.
[0058] The mass ratio of the terephthalic acid, ethylene glycol, stabilizer dispersion, catalyst dispersion and silicon dioxide dispersion is 50:20:1:0.1:0.5.
[0059] Comparative Example 1
[0060] A method for preparing a polyester masterbatch suitable for a low-roughness PET optical film, the preparation method comprising the following steps:
[0061] S1. Prepare stabilizer dispersion, catalyst dispersion and silicon dioxide dispersion respectively for standby use;
[0062] S2. Evenly mix terephthalic acid and ethylene glycol and carry out esterification reaction at 255° C. and 0.3 MPa to obtain esterified liquid; when the amount of esterified water collected reaches 90%, the esterified liquid is transferred to a pre-condensation reactor.
[0063] S3, adding stabilizer dispersion, catalyst dispersion and silica dispersion to the esterification liquid in a pre-polycondensation reactor, and performing a pre-polycondensation reaction at 275° C. and 100 kPa to obtain an intermediate, and the reaction time is 30 min; the esterification liquid is not circulated during the pre-polycondensation reaction;
[0064] S4. The intermediate prepared by the pre-polycondensation reaction is subjected to a final polycondensation reaction at 285° C. and 50 PaA to obtain a melt, and the melt is pelletized and packaged to obtain a polyester masterbatch.
[0065] The mass ratio of the terephthalic acid, ethylene glycol, stabilizer dispersion, catalyst dispersion and silicon dioxide dispersion is 50:20:1:0.1:0.5.
[0066] Comparative Example 2
[0067] A method for preparing a polyester masterbatch suitable for a low-roughness PET optical film, the preparation method comprising the following steps:
[0068] S1. Prepare stabilizer dispersion liquid and catalyst dispersion liquid separately for standby use;
[0069] S2, adding ethylene glycol into a preparation tank equipped with a stirrer, then adding silicon dioxide into the ethylene glycol, stirring at a speed of 1500 m / min for 0.5 to 2.5 h to prepare a silicon dioxide dispersion;
[0070] S2. Evenly mix terephthalic acid and ethylene glycol and carry out esterification reaction at 255° C. and 0.3 MPa to obtain esterified liquid; when the amount of esterified water collected reaches 90%, the esterified liquid is transferred to a pre-condensation reactor.
[0071] S3, adding stabilizer dispersion, catalyst dispersion and silica dispersion to the esterification liquid in a pre-polycondensation reactor, and performing a pre-polycondensation reaction at 275° C. and 100 kPa to obtain an intermediate, and the reaction time is 30 min; the esterification liquid is not circulated during the pre-polycondensation reaction;
[0072] S4. The intermediate prepared by the pre-polycondensation reaction is subjected to a final polycondensation reaction at 285° C. and 50 PaA to obtain a melt, and the melt is pelletized and packaged to obtain a polyester masterbatch.
[0073] The mass ratio of the terephthalic acid, ethylene glycol, stabilizer dispersion, catalyst dispersion and silicon dioxide dispersion is 50:20:1:0.1:0.5.
[0074] Performance and testing:
[0075] a. The performance indicators of the polyester masterbatch suitable for low-roughness PET optical film prepared by the present invention are: intrinsic viscosity of 0.635-0.655 dl / g, terminal carboxyl content of 22-28 mol / t, L value of 88-89 (without adding silicon dioxide), and diethylene glycol content of 1.2-1.5%.
[0076] b. The silica dispersion of the present invention has uniform particle distribution and concentrated particle size distribution. The particle size distribution diagram is as follows Figure 2 As shown; the silicon dioxide dispersion prepared in Comparative Example 2 is as Figure 3 As shown:
[0077] c. The polyester masterbatch and preparation process for low-roughness PET optical film prepared by the present invention, after biaxial stretching film formation, the film surface particles are evenly distributed and the particle size distribution is concentrated, and the surface roughness Sa≤15nm, Sz≤15μm, the surface roughness measurement of Example 1 is as follows Figure 5 As shown; Comparative Example 1 Surface roughness measurement as shown Figure 6 As shown; Comparative Example 2 Surface roughness measurement as shown Figure 7 As shown:
[0078]
[0079] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0080] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A method for preparing a polyester masterbatch suitable for a low-roughness PET optical film, characterized in that: The preparation method comprises the following steps: S1. Prepare stabilizer dispersion, catalyst dispersion and silicon dioxide dispersion respectively for standby use; S2, terephthalic acid and ethylene glycol are mixed uniformly and subjected to esterification reaction at 240-255° C. and 0.3 MPa to obtain esterified liquid; when the amount of esterified water collected reaches 90%, the esterified liquid is transferred to a pre-condensation reactor; S3, in the pre-polycondensation reactor, adding the stabilizer dispersion, the catalyst dispersion and the silica dispersion to the esterification liquid in sequence, and performing a pre-polycondensation reaction at 255-275° C. and 10-100 kPa to obtain an intermediate, and the reaction time is 30-45 min; the esterification liquid is always circulated during the pre-polycondensation reaction; S4. The intermediate prepared by the pre-polycondensation reaction is subjected to a final polycondensation reaction at 275-285° C. and 30-50 PaA to obtain a melt, and the melt is pelletized and packaged to obtain a polyester masterbatch.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the terephthalic acid, ethylene glycol, stabilizer dispersion, catalyst dispersion and silicon dioxide dispersion is (50-70):(20-30):(1-5):(0.1-1):(0.5-25).
3. The preparation method according to claim 1, characterized in that: The catalyst dispersion is specifically configured as follows: ethylene glycol is added to a preparation tank with an agitator, and then the catalyst is added to the ethylene glycol, heated to 130-170°C, and stirred at a speed of 250-1000 m / min for 0.5-1.5 hours; after the stirring is completed, the material is transferred to the intermediate tank through a homogenizing and dispersing device, and after all the materials are transferred to the intermediate tank, all the materials are transferred to the preparation tank, and the materials are transferred to the intermediate tank again through the homogenizing and dispersing device, and the process is repeated 2-5 times to prepare the catalyst dispersion.
4. The preparation method according to claim 3, characterized in that: The mass proportion of the catalyst in the catalyst dispersion is 1-5%; the catalyst is one of antimony-based, titanium-based, germanium-based or composite catalysts.
5. The preparation method according to claim 1, characterized in that: The specific configuration of the stabilizer dispersion is as follows: ethylene glycol is added into a preparation tank with a stirrer, and then the stabilizer is added into the ethylene glycol, and stirred at a speed of 250 to 1000 m / min for 0.5 to 1.5 h to prepare the stabilizer dispersion.
6. The preparation method according to claim 5, characterized in that: The mass proportion of the stabilizer in the stabilizer dispersion is 1-10%; the stabilizer is one of phosphoric acid, trimethyl phosphate, triethyl phosphate and triphenyl phosphate.
7. The preparation method according to claim 1, characterized in that: The silica dispersion is specifically configured as follows: ethylene glycol is added to a preparation tank with a stirrer, and then silica is added to the ethylene glycol, and stirred at a speed of 500-1500 m / min for 0.5-2.5 hours; after the stirring is completed, the material is transferred to the intermediate tank through homogenization and dispersion, and after all the materials are transferred to the intermediate tank, all the materials are transferred to the preparation tank, and the materials are transferred to the intermediate tank again through the homogenization and dispersion equipment, and the process is repeated 2-5 times to prepare a silica pre-dispersion liquid, and the silica pre-dispersion liquid is transferred to the finished product tank after centrifugation in a centrifuge to prepare a silica dispersion liquid; the centrifuge drum speed is 1500-3000 r / min, and the centrifugal force is 2000-3500 xg.
8. The preparation method according to claim 7, characterized in that: The mass proportion of silicon dioxide in the silicon dioxide dispersion is 7-15%.
9. A polyester masterbatch suitable for low-roughness PET optical film prepared by the preparation method of a polyester masterbatch suitable for low-roughness PET optical film according to any one of claims 1 to 8.
10. The polyester masterbatch suitable for low-roughness PET optical film as claimed in claim 9 is used as a raw material in the preparation of optical film materials.
Citation Information
Patent Citations
Polyester master batch special for MLCC release film and preparation method of polyester master batch
CN115322533A